The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1136/bmjopen-2020-046532
|View full text |Cite
|
Sign up to set email alerts
|

Work stress and oral conditions: a systematic review of observational studies

Abstract: ObjectivesAlthough psychological stress is a risk factor for oral diseases, there seems to be no review on work stress. This study aimed to review the evidence on the association between work stress and oral conditions, including dental caries, periodontal status and tooth loss.DesignA systematic review of published observational studies.Data sourcesA systematic literature search was conducted in PubMed and Scopus databases on 12 August 2020.Study selectionArticles were screened based on the following inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
(67 reference statements)
1
10
0
Order By: Relevance
“…Work stress was associated with an increased risk of poor periodontal status, which is consistent with previous studies ( Sato, Saijo & Yoshioka, 2021 ). Eight of nine previous studies reported a significant association between work stress and periodontal status, but only one study used the accepted measure for work stress and adjusted for potential confounders ( Segura Marcenes & Sheiham, 1992 ; Sato, Saijo & Yoshioka, 2021 ). Our results support the previous study results.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Work stress was associated with an increased risk of poor periodontal status, which is consistent with previous studies ( Sato, Saijo & Yoshioka, 2021 ). Eight of nine previous studies reported a significant association between work stress and periodontal status, but only one study used the accepted measure for work stress and adjusted for potential confounders ( Segura Marcenes & Sheiham, 1992 ; Sato, Saijo & Yoshioka, 2021 ). Our results support the previous study results.…”
Section: Discussionsupporting
confidence: 92%
“…The current results show a negative association between work stress and the number of decayed and filled teeth (caries experienced teeth). There is only one previous study on work stress and the number of teeth with caries ( Segura Marcenes & Sheiham, 1992 ; Sato, Saijo & Yoshioka, 2021 ). In a previous study, work stress was assessed using the demand-control model, and the dependent variable was DMF tooth surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations